2016
DOI: 10.1590/1516-4446-2015-1899
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inflammatory biomarkers and depressive symptoms during late pregnancy and the early postpartum period: a longitudinal study

Abstract: Objective: Perinatal depressive symptoms often co-occur with other inflammatory morbidities of pregnancy. The goals of our study were 1) to examine whether changes in inflammatory markers from the third trimester of pregnancy to 12 weeks postpartum were associated with changes in depressive symptoms; 2) to examine whether third trimester inflammatory markers alone were predictive of postpartum depressive symptoms; and 3) to examine the relationship between inflammatory markers and depressive symptoms during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 30 publications
7
52
0
10
Order By: Relevance
“…For example, depression increases sympathetic nervous system tone [19]. Additionally, numerous studies link inflammation to depression in non-pregnant adults [20] [21], yet pregnancy-specific studies are notably less consistent in the association between inflammatory markers and depression [22] [23]. Our findings further support the association between hypertension and depression in pregnancy, and they strengthen the need for further mechanistic studies.…”
Section: Discussionsupporting
confidence: 56%
“…For example, depression increases sympathetic nervous system tone [19]. Additionally, numerous studies link inflammation to depression in non-pregnant adults [20] [21], yet pregnancy-specific studies are notably less consistent in the association between inflammatory markers and depression [22] [23]. Our findings further support the association between hypertension and depression in pregnancy, and they strengthen the need for further mechanistic studies.…”
Section: Discussionsupporting
confidence: 56%
“…Cassidy-Bushrow and colleagues 58 similarly did not find any association between CRP concentrations and depressive symptoms in a sample of 187 pregnant women who were between 13–28 weeks gestation. Of two smaller studies, one with an N of 27 59 found an increase in CRP with depressive symptoms at both 35–38 weeks gestation and at 1–5 days postpartum, though not at 5–6 weeks postpartum; while another with an N of 31 60 found no association of CRP with depressive symptoms, either at 26+ weeks gestation or at 12 weeks postpartum. Given the disparate timeframes within which these studies were conducted, it is difficult to draw any solid conclusions; however taken together they suggest that CRP elevation is not a consistent feature of perinatal depression.…”
Section: Depression and Inflammation In The Perinatal Periodmentioning
confidence: 90%
“…Two studies reported a negative association (N=105, 16–26 weeks gestation 70 ;and N=152, significant at all six postpartum timepoints measured 69 ). Three studies reported no association (N=31, 26+ wk gestation and postpartum 60 ; N=18, 13–28 weeks gestation 58 ; N=145, 18 and 32 weeks gestation 66 ).…”
Section: Depression and Inflammation In The Perinatal Periodmentioning
confidence: 96%
See 2 more Smart Citations